Comparison of the Frontal Plane Projection Angle and the Dynamic Valgus Index to Identify Movement Dysfunction in Females with Patellofemoral Pain - Lori A Bolgla; Haley N Gibson; Daniel C Hannah; Tiana Curry-McCoy (North American Sports Medicine Institute, 2023)
# Background Clinicians typically measure the knee frontal plane projection angle (FPPA) during a single-leg squat to identify females with patellofemoral pain (PFP). A limitation of this measure is minimal attention to movement of the pelvis on the femur that can create knee valgus loading. The dynamic valgus index (DVI) may be a better assessment. # Hypothesis/Purpose The purpose of this study was to compare the knee FPPA and DVI between females with and without PFP and determine if the DVI better identified females with PFP than the knee FPPA. # Study Design Case-control # Methods Sixteen females with and 16 without PFP underwent 2-dimensional motion analysis when performing five trials of a single-leg squat. The average peak knee FPPA and peak DVI were analyzed. Independent *t*-tests determined between-group peak knee FPPA and peak DVI differences. Receiver operating characteristic (ROC) curves determined the area under the curve (AUC) scores for sensitivity and 1 - specificity of each measure. Paired-sample area difference under the ROC curves was conducted to determine differences in the AUC for the knee FPPA and DVI. Positive likelihood ratios were calculated for each measure. The significance level was *p* \< 0.05. # Results Females with PFP exhibited a higher knee FPPA (*p* = 0.001) and DVI (*p* = 0.015) than controls. AUC scores were .85 (*p* = 0.001) and .76 (*p* = 0.012) for the knee FPPA and DVI, respectively. Paired-sample area difference under the ROC curves showed a similar (*p* = 0.10) AUC for the knee FPPA and DVI. The knee FPPA had 87.5% sensitivity and 68.8% specificity; the DVI had 81.3% sensitivity and 81.0% specificity. Positive likelihood ratios for the knee FPPA and DVI were 2.8 and 4.3, respectively. # Conclusion The DVI during a single-leg squat may be another useful tool for discriminating between females with and without PFP. # Level of Evidence 3a